2020
DOI: 10.3390/ani10040579
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Slaughter Knife Sharpness on Blood Biochemical and Electroencephalogram Changes in Cattle

Abstract: The sharpness of the knife used for slaughter is of the utmost importance from an animal welfare perspective. The quantification of knife sharpness is almost impossible in abattoirs. The sharpness of the knife blade used to slaughter an animal, as well as its effects on animals’ pain and stress levels, is an important area of investigation that needs to be addressed. The objective of this study was to evaluate the effects of knife sharpness on blood biochemical parameters, plasma catecholamines, and electroenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 57 publications
0
33
0
1
Order By: Relevance
“…Lesions or trauma also stimulate a neuroendocrine reaction due to the intricate connections between the two systems. This reaction has three components: (1) the sympathetic-adrenomedullary (SAM) response mediated by catecholamines such as dopamine, noradrenaline and adrenaline, (2) Corticotropin-releasing hormone (CRH) activation of the hypothalamic-pituitary-adrenal (HPA) axis leading to production of glucocorticoids and (3) activation of the locus coeruleus and the noradrenergic limbic brain [ 2 , 23 , 24 ]. Limbic structures, including the hippocampus, amygdala and pre-frontal cortex have an inhibitory influence by resetting the HPA axis following a stressful event [ 25 ].…”
Section: The Neurobiology Of Painmentioning
confidence: 99%
See 3 more Smart Citations
“…Lesions or trauma also stimulate a neuroendocrine reaction due to the intricate connections between the two systems. This reaction has three components: (1) the sympathetic-adrenomedullary (SAM) response mediated by catecholamines such as dopamine, noradrenaline and adrenaline, (2) Corticotropin-releasing hormone (CRH) activation of the hypothalamic-pituitary-adrenal (HPA) axis leading to production of glucocorticoids and (3) activation of the locus coeruleus and the noradrenergic limbic brain [ 2 , 23 , 24 ]. Limbic structures, including the hippocampus, amygdala and pre-frontal cortex have an inhibitory influence by resetting the HPA axis following a stressful event [ 25 ].…”
Section: The Neurobiology Of Painmentioning
confidence: 99%
“…It has been suggested that following sticking in cattle, consciousness may last for 60 s or more [ 54 ]. During this period there is potential for animals to experience both pain and distress due to transection of a series of nociceptive fibers, that when activated generate a stream of sensory impulses that make pain perception inevitable [ 2 ]. In most jurisdictions, regulatory and guidance documents require that steps are put in place to mitigate the experience of pain associated with sticking.…”
Section: Hyperalgesia and Events At Slaughtermentioning
confidence: 99%
See 2 more Smart Citations
“…The origin of this hazard is identified to be lack of skilled operator and too short and /or blunt knife. Recently, Imlan et al (2020) evaluated the effects of knife sharpness on EEG responses in cattle. The results showed a significant increase in the median frequency and total power of the EEG, the parameters indicative of pain and distress, in the animals slaughtered without stunning by cutting soft tissues in the neck at the first cervical vertebra.…”
Section: Repeated Cutsmentioning
confidence: 99%